2016
DOI: 10.5897/jpp2015.0366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-bacterial activity and bioactive chemical analysis of Ocimum basilicum using Fourier transform infrared (FT-IR) and gas chromatography-mass spectrometry (GC-MS) techniques

Abstract: The objective of this research was to determine the chemical composition of aerial parts extract from methanol. The phytochemical compound screened by gas chromatography-mass spectrometry (GC-MS) method. Thirty one bioactive phytochemical compounds were identified in the methanolic extract of Ocimum basilicum. The identification of phytochemical compounds is based on the peak area, retention time molecular weight, molecular formula, MS fragment-ions and pharmacological actions. GC-MS and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…Of all the extracts tested methanol leaf extracts proved to be the best for E. coli with 29.0 mm zone of inhibition while stem extract has the lowest zone of inhibition of 17mm on Intestinal enterococcus. However, these results are in accordance with studies that had reported that the methanol extract of A. paniculata showed antibacterial activity against E. coli [79,80]. Also in another study by Sharma et al [81], it was found that the MIC of Camellia sinensis and Andrographis paniculata extract was found to be 200 μg/mL against exponentially growing VRE.…”
Section: Antibacterial Activity Of a Paniculata Against The Enteric supporting
confidence: 90%
“…Of all the extracts tested methanol leaf extracts proved to be the best for E. coli with 29.0 mm zone of inhibition while stem extract has the lowest zone of inhibition of 17mm on Intestinal enterococcus. However, these results are in accordance with studies that had reported that the methanol extract of A. paniculata showed antibacterial activity against E. coli [79,80]. Also in another study by Sharma et al [81], it was found that the MIC of Camellia sinensis and Andrographis paniculata extract was found to be 200 μg/mL against exponentially growing VRE.…”
Section: Antibacterial Activity Of a Paniculata Against The Enteric supporting
confidence: 90%
“…The incorporation of F. cernua into the nanolaminates delayed the weight loss of the fruit, when compared with the nanolaminates without the extract. This tendency in the weight loss during storage, is natural, as the loss occurs mainly by the transpiration process (Souza et al, 2014;Flores-López et al, 2016a;Mohanad et al, 2016). However, a loss higher than 5% is a restricting factor for the fruit marketing and consumption (Aktas et al, 2012).…”
Section: Weight Lossmentioning
confidence: 99%
“…It was also detected as a major constituent in essential oils and methanol extract. 52,53 The inhibitory effect of O. basilicum on MDA-MB-435 cells could be strongly attributed to their higher contents of methyl eugenol (40.58%) and phytol (6.03%). Methyl eugenol demonstrated cytotoxic and antimigratory effects against the MDA-MB-231 breast cell line.…”
Section: Resultsmentioning
confidence: 99%